Bilateral internal thoracic artery coronary bypass grafting - D. V. Kuznetsov; A. A. Gevorgyan; V. V. Novokshenov; K. M. Mikhailov; A. V. Kryukov; S. M. Khokhlunov (Вестник хирургии имени И.И. Грекова)
The OBJECTIVE of the study was to assess the immediate results of the use of two internal thoracic arteries during coronary bypass surgery.MATERIAL AND METHODS. 200 patients with coronary artery disease underwent coronary artery bypass grafting in Samara cardiology dispensary from 2016 to 2018. Patients were divided into 2 groups. Group 1 (100 people) used both internal thoracic arteries (ITA) and the radial artery as conduits; group 2 (100 people) used the left ITA and the great saphenous vein as conduits. The duration of the operation, complications in the early postoperative period, and hospital mortality were evaluated.RESULTS. Groups (1 – 73 % of men, average age (59±12) years, average number of conduits – (3.1±0.4), 2 – 62 % of men, average age (67±7) years, average number of conduits – (3.3±0.6)) were significantly different only in age. The average duration of the operation in the group 1 was (174±25) min, in 2 – (165±18) min (p<0.05). Hospital mortality in the group 1 – 0 %, in 2 – 1 % (p>0.05). The number of complications in the early postoperative period did not have a statistically significant difference between the groups.CONCLUSION. Bilateral internal thoracic arteries coronary artery bypass grafting in CHD patients did not lead to a significant increase in the duration of the operation, an increase in mortality and infectious  complications from the sternum, compared with single internal thoracic arteries grafting.